Effects of Y Dopant on Lattice Distortion and Electrical Properties of In3SbTe2 Phase‐Change Material. Issue 11 (20th September 2017) - Choi, Minho; Choi, Heechae; Kwon, Sehyun; Kim, Seungchul; Lee, Kwang‐Ryeol; Ahn, Jinho; Kim, Yong Tae
Abstract : Using a computational high‐throughput screening method, 29 doping elements have been investigated for improving the thermal and electrical characteristics of In3 SbTe2 (IST) phase‐change material. Among the 29 dopants, it is found that Y offers largest distortion in the lattice structure of IST with negative doping formation energy while Y substitutes the In site. The atomic lattice images clearly show that the In site is substituted by Y and the distortion angles of the Y‐doped IST (Y‐IST) are well matched with the calculated results of density functional theory (DFT). Set/reset speed of the Y‐IST phase‐change memory is faster than IST and Ge2 Sb2 Te5 (GST) devices, which is strongly related with the fast and stable phase transition due to the larger lattice distortion. The power consumption of the Y‐IST device is also less than a fourth of that of the GST device. Abstract : Twenty‐nine elements were selected to find proper dopants for large distortion in In3 SbTe2 phase‐change material as a substitutional atom. Yttrium was chosen as the best dopant in In3 SbTe2 using a computational high‐throughput screening method. Experimentally, the yttrium substitution improved the operation speed and power consumption with fast transition between amorphous and crystalline phases.